The Relationship between Entrepreneurial Attitude, Entrepreneurial Education, and Entrepreneurial Intentions of Millennial College Students, Entrepreneurial Self-Efficacy as a Mediator - Tian, Feng; Tan, Helen Sui-Hong; Yang, Yi-Ting (Business Management and Strategy, 2025)
Due to the development and reform of the social economy, entrepreneurship has become a career choice for many college graduates. The study aims to examine the factors that influence entrepreneurial intentions among millennial college students in Jinan, Shandong Province, China. A total of 405 valid questionnaires were collected as the sample, and the data were analyzed using SPSS version 27 to assess correlations and effects. In addition to the primary data, secondary sources, including research articles and online resources, were consulted for further insights. The results indicated that entrepreneurial attitude, entrepreneurial education, and entrepreneurial self-efficacy have a positive impact on entrepreneurial intention, with entrepreneurial self-efficacy being the most significant factor. The value of the research lies in providing insights for educational institutions, policymakers, and support organizations to foster entrepreneurship among millennials. Future research should consider larger samples, diverse data collection methods such as offline research and interviews, and longitudinal studies for deeper understanding of and guidance for entrepreneurial development.